Determinants of health status and health-related behaviors among polish firefighters: a nationwide survey-based study - Dudziński, Łukasz; Tymiński, Jan; Kubiak, Tomasz; Czyzewski, Lukasz; Wyzgal, Janusz; Gałązkowski, Robert (Frontiers in Nutrition, 2025)
ObjectiveTo assess health practices among Polish firefighters in relation to the high physical and mental demands of their profession.Materials and methodsA cross-sectional survey design with categorical data analysis was used. An online survey was conducted between 10 October 2024 and 25 October 2024. The survey covered 856 officers serving in organisational units of the State Fire Service (SFS) throughout Poland. The survey was based on a proprietary questionnaire, including demographics and individual health practices: nutrition, stimulants, sleep, physical activity.ResultsEight hundred seventeen respondents who answered all questions were included in the analysis. The analysis of the results did not show any statistically significant differences between the genders in terms of: participation in sports/physical activity (yes vs. no) (p = 0.088); frequency of physical activity (p = 0.541); type of diet (p = 0.741). Persons employed in command positions were the least likely to smoke cigarettes (p < 0.001). These people most often indicated that they were very satisfied with their health (p < 0.001). People in command positions were more likely to declare unhealthy eating habits, but at the same time they assessed their health better.ConclusionThis nationwide survey identified clear, actionable patterns in firefighters’ health behaviors. Overweight and obesity were common, and multiple behaviors clustered with higher BMI. Prevention should be targeted across career stages and supported organizationally integrating nutrition, hydration, sleep hygiene, and physical training with enabling conditions (duty scheduling, healthy food/water access on shift, protected time and facilities for exercise). Future studies should include objective measurements, validated psychosocial scales, and longitudinal designs to clarify directionality and evaluate interventions.